Family-Centred Nursing Theory and the Functional Consequences Model Improve Diabetes Self-Management in Elderly Diabetics - Vitaliati, Trisna; Silvanasari, Irwina Angelia; Maurida, Nurul; Basri, Ahmad Ali (JKG (JURNAL KEPERAWATAN GLOBAL), 2024)
Background: The self-care management of older diabetics is inconsistent and exhibits low adherence. This incident may be influenced by the elderly's disease management capabilities and familial involvement, which may not be conducive to their health and care. This study aimed to develop a management plan for elderly diabetes mellitus that emphasizes self-efficacy and family involvement. Methods: This research employed an explanatory survey design with a cross-sectional methodology. The probability sampling method, particularly simple random sampling, was employed to choose respondents for this study from a cohort of 100 individuals with diabetes mellitus and their families. We created a thorough assessment questionnaire for diabetes mellitus management in the elderly, utilizing the functional consequence model and family-centred nursing theory as the research framework. The statistical method employed was SEM-PLS. Results: The outer model analysis revealed that all indicators of each construct were valid, with a factor loading value of > 0.7. The inner model analysis revealed that the variables family structure, family function, family stressors, elderly risk factors, age-related changes, and elderly consequence functions had a significant effect with a t-value of >1.96 and p-value <0.05. Conclusion: The diabetic mellitus management model, which is based on self-efficacy and familial support, improves self-care management among the elderly. Nurses should adopt the diabetic mellitus management model to increase patient autonomy and educate families on how to support their loved ones, thereby improving the self-care practices of elderly adults with diabetes.